1134 Incidence of Bile Acid Diarrhoea Post-Cholecystectomy - A Single Centre Cohort. (12th October 2021) - Sallam, M; Patel, R; Sun, W; Ali, R; Windle, R; Shalaby, S; Ward, J; Bond-smith, G
Abstract: Aim: Bile acid diarrhoea (BAD) can occur as a result of enterohepatic circulation interruption following cholecystectomy. Although up to 57.2% of patients are reported to develop post-cholecystectomy diarrhoea, this is not always because of BAD. The aim of this study was to determine the incidence of post-cholecystectomy BAD diagnosis and evaluate the current practices. Method: This study was conducted as part of BADCAP study. The electronic records of patients underwent cholecystectomy operation at Oxford University Hospitals between January 2013 and December 2017 were retrospectively analysed. Records were matched with patients who underwent 75SeHCAT testing during the same time period. A positive 75SeHCAT testing was defined as a seven-day retention time of < 15%. Results: A total of 4327 patients underwent cholecystectomy operation. 2.05% (N = 89) investigated for diarrhoea by 75SeHCAT. Alongside 75SeHCAT, 69.7% (N = 62) had colonoscopy, 37.1% (N = 33) had CT abdomen and pelvis and 3.4% (N = 3) had MRCP/MRE. Gender wise statistics revealed females were 74.5% (N = 73) and males were 19.1% (N = 17). Median time from cholecystectomy to 75SeHCAT test was 780 days (SD +/-510 days). 70.8% (N = 63) had a positive 75SeHCAT test for BAD. IBD was confirmed in 2.2% (N = 2). Conclusions: A small number of patients were investigated and only 1.5% were diagnosed with post-cholecystectomy diarrhoea. There was a significant time delay from operation to diagnosis. The true prevalence of BAD after cholecystectomy may be much higher and clinicians need to have an increased awareness of this condition. 75SeHCAT is a useful tool for diagnosis of bile acid diarrhoea.